Productivity growth of zakat institutions in Malaysia: An application of data envelopment analysis - Abd. Wahab, Norazlina; Abdul Rahman, Abdul Rahim (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to analyze the changes in productivity of zakat institutions in Malaysia from 2003 to 2007. The data consist of a panel of 14 State Islamic Religious Councils (SIRCs) in Malaysia. Efficiency is measured by the Malmquist Index, using a data envelopment analysis (DEA) technique.